Various theories explaining why the Jewish people are special : a response to Jerome Gellman, David Novak, and Michael Wyschogrod's understanding of the chosen people - Gluck, Andrew Lee (Lewiston : The Edwin Mellen Press, 2016)
"The author offers observations from the Jewish point of view, accentuating the need for Christians, Jews, and all humanity to see each other more as separated brethren than conquerors of doctrinal disputes or combatants on the literal fields of history with a greater understanding of Jewish heritage in the Western world and the need to preserve the worldview specially granted to the Jews historically"--
Includes bibliographical references (pages 397-409) and indexes.
Print version record.
Master record variable field(s) change: 600
Keywords: Gellman, Jerome I; Novak, David, -- 1941-; Wyschogrod, Michael, -- 1928-; Jews -- Election, Doctrine of; RELIGION / Judaism / General; Jews -- Election, Doctrine of; Electronic books